Sloshing in a tank of a ship at sea: full scale surveys and analysis - CARRERA, GIOVANNI; RIZZUTO, ENRICO; TEDESCHI, RODOLFO (1994)
In this paper a survey of the dynamic pressures generated in a ballast tank of a bulk carrier ship during a voyage in the North-Atlantic Ocean is described. A frequency of 4 Hz was adopted for the surveys of ship motions, structural strains, and pressure fluctuations due to the motion of the water inside the tank. Particular attention was devoted to the survey of impulsive events in the fluid-structure interaction, with a higher sampling frequency (20kHz) adopted for the pressure transducers inside the tank in the proximity of the pulses. A description of the instrumentation and the survey procedures utilized in the test is reported. The results were analysed in terms of time histories and histograms of the various quantities as well as in the frequency domain.